Environmental Taxation as a Policy Instrument for Green Growth - Maksym Klymenko (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article is devoted to environmental taxation as a tool for green growth and assistant to solve environmental issues of the world and Ukraine in particular. Nowadays, the world's economic growth goes side by side with environmental protection, and taxation aims to become an economic instrument to stop large-scale over-use of energy and consider effective resource utilisation, expand the share of organic farming and move towards “green” economy. The paper identifies the main groups of environmental taxes in the EU countries, analyses the European experience of the economic impact on the environment protection, examines possible ways of environmental taxation reforming in Ukraine, based on successful foreign experience.